Serological evidence of canine arthropod-borne infections in an ecotone area of a natural reserve at the Pantanal, Brazil - Alberigi, Bruno; Labarthe, Norma; Cardoso, Flavia; Cunha, Caroline; Almeida, Caroline; Souza, Celeste; Mendes-de-Almeida, Flavya (Brazilian Journal of Veterinary Medicine, 2019)
Arthropod-borne infections are dependent on environmental conditions; therefore, anthropomorphic meddling may disrupt the natural balance that maintains wildlife. It is common to find dogs roaming in Brazilian natural reserves, what favors the spillover of pathogens among species. The aim of this study was to determine the canine seroprevalence of Ehrlichia canis, E. ewingii, Anaplasma platys, A. phagocytophilum, Borrelia burgdorferi, Leishmania infantum and Dirofilaria immitis using 84 serum samples from dogs from the border area of the SESC-Pantanal reserve (RPPN SESC-Pantanal 16°40 ́51 ́ ́S;56o17 ́45 ́ ́W) stored at the Laboratório de Protozoologia e Imunomodulação, Instituto Oswaldo Cruz. Samples were tested with SNAP Canine Leishmania Antibody Test (IDEXX Laboratories) or DPP canine visceral leishmaniasis test (Bio-Manguinhos) for the presence of L. infantum antibodies and with SNAP 4Dx Plus Test (IDEXX Laboratories) for D. immitis, Ehrlichia spp., Anaplasma spp. and B. burgdorferi seroprevalences. The seroprevalence for tick-borne parasites was 79.8%, 13.1% for L. infantum and 7.1% for D. immitis. Since tick-borne parasites were the most frequent among the examined dogs it may be suggested that these parasites, ticks and hosts display special resilience skills to overcome the hostile local conditions. The low L. infantum prevalence suggests that the local biodiversity, especially the bird abundance, depurates Leishmania circulation. The mosquito-borne D. immitis prevalence was higher than expected, suggesting that the local flooding regime provides suitable mosquito-breeding spots. On the other hand, the only known vector in the area feeds on birds, therefore reducing mosquitoes worm burden and imparing D. immitis transmission.